(untitled) (BIRDEM Medical Journal, 2016)
Background: Fiber-optic bronchoscopy (FOB) is an invasive procedure performed to identify possible endobronchial lesions. Diabetic patients often present with non-resolving pneumonia and collapse, many of whom are elderly and smoker; thus always giving rise to the suspicion of malignancy. Methods: This observational study was performed from March 2009 to August 2013 in the Department of Internal Medicine and Pulmonology of BIRDEM General Hospital, Dhaka, Bangladesh; a 500 bedded tertiary care hospital dealing mostly with diabetic patients. Results: Out of 160 diabetic patients 126 (78.7%) were male, 34 (21.3%) were female. Mean age of the patients was 57.2 ±10.8 years. The indications of bronchoscopy were collapse (38, 23.8%), non-resolving consolidation (55, 34.4%), mass lesion (38, 23.8%), hemoptysis (10, 6.2%) and others (19, 11.8%). Findings in the bronchoscopy were mitotic lesion (56, 35.0%), inflammatory lesion (50, 31.3%) and normal finding (54, 33.8%). Among 56 cases of mitotic lesion, bronchial biopsy was taken in 48 (85.7%) cases. Histopathology reports of bronchial biopsy were squamous cell carcinoma (18, 37.5%), large cell carcinoma (11, 22.9%), adenocarcinoma (7, 14.6%), small cell carcinoma (5, 10.4%), inflammatory lesion (4, 8.3%) and normal finding (3, 6.3%). Among 38 cases of collapse, mitotic lesion was found in 24 (63.2%) cases. Among 55 (100%) cases of non-resolving consolidation, mitotic lesion was found in 18 (32.5%), inflammation in 23 (41.8%) and normal findings in 14 (25.5%) cases. Conclusion: Bronchoscopy is an useful method to detect any endobronchial lesion in suspected cases of collapse or non-resolving pneumonia in diabetic patients and it can be the choice of investigation in non-resolving pneumonia. Birdem Med J 2016; 6(1): 18-21